Tenascin-C in Osteoarthritis and Rheumatoid Arthritis - Hasegawa, Masahiro; Yoshida, Toshimichi; Sudo, Akihiro (Frontiers in Immunology, 2020)
Tenascin-C (TNC) is a large multimodular glycoprotein of the extracellular matrix that consists of four distinct domains. Emerging evidence suggests that TNC may be involved in the pathogenesis of osteoarthritis (OA) and rheumatoid arthritis (RA). In this review, we summarize the current understanding of the role of TNC in cartilage and in synovial biology, across both OA and RA. TNC is expressed in association with the development of articular cartilage; the expression decreases during maturation of chondrocytes and disappears almost completely in adult articular cartilage. TNC expression is increased in diseased cartilage, synovium, and synovial fluid in OA and RA. In addition, elevated circulating TNC levels have been detected in the blood of RA patients. Thus, TNC could be used as a novel biochemical marker for OA and RA, although it has no specificity as a biochemical marker for these joint disorders. In a post-traumatic OA model of aged joints, TNC deficiency was shown to enhance cartilage degeneration. Treatment with TNC domains results in different, domain-specific effects, which are also dose-dependent. For instance, some TNC fragments including the fibrinogen-like globe domain might function as endogenous inducers of synovitis and cartilage matrix degradation through binding with toll-like receptor-4, while full-length TNC promotes cartilage repair and prevents the development of OA without exacerbating synovitis. The TNC peptide TNIIIA2 also prevents cartilage degeneration without causing synovial inflammation. The clinical significance of TNC effects on cartilage and synovium is unclear and understanding the clinical significance of TNC is not straightforward.